Successful Treatment of Infraorbital Trapdoor Following Transposition Flap Using Intralesional Corticosteroid: A Case Report - Khairuddin Djawad (Wolters Kluwer Health, 2021)
Abstract. Introduction:. The trapdoor effect can pose a significant cosmetic issue after transposition flap surgery or trauma. It is characterized with bulging of tissue around a circular or semi-circular scar commonly found after removal of cutaneous tumors. Here, we report a female with infraorbital trapdoor successfully treated by intralesional corticosteroid. Case presentation:. A 60-year-old female patient with trapdoor effect after surgery was successfully treated with long-term non-invasive technique of intralesional triamcinolone acetate set with a biweekly interval for twelve months. Discussion:. There are currently no definitive methods of removing this condition. Non-surgical approach is often more preferred by patients, such as with the use of intralesional corticosteroid of triamcinolone acetate. However, information about this is still limited. In this case, the patient experienced satisfying result without observed complications related to corticosteroids injection on the infraorbital region. Conclusion:. Intralesional corticosteroid is a safe and economical method to treat the trapdoor effect.